1985
DOI: 10.1111/j.1476-5381.1985.tb11113.x
|View full text |Cite
|
Sign up to set email alerts
|

Cholinesterase activity and exposure time to acetylcholine as factors influencing the muscarinic inhibition of [3H]‐noradrenaline overflow from guinea‐ pig isolated atria

Abstract: 1 Guinea-pig isolated atria were incubated and loaded with [3H]-noradrenaline. The release of 3H and of [3H]-noradrenaline was induced by field stimulation (6-9 trains of 150 pulses at 5 Hz). The stimulation-evoked overflows of 3H and of [3H]-noradrenaline were determined. 2 In the absence of an inhibitor of acetylcholinesterase, acetylcholine (12 min preincubation before nerve stimulation, up to 10pM) failed to inhibit the evoked [3H]-noradrenaline overflow. In the presence of atropine, an increase by acetylc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
1989
1989

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…(Daemen et al, 1989) (Muscholl et al, 1979). Fuder et al (1985) also demonstrated an inhibition of the NA overflow using this selective muscarinic agonist at concentrations of 1 and 10 M in guinea-pig isolated atria. In our model, infusion of MCh (0.3pgmin-1) has no effect on the basal NA level, indicating that possible interfering effects of MCh like vasodilatation or bradycardia have no influence on the plasma NA level measured in the portal vein.…”
Section: Discussionmentioning
confidence: 76%
“…(Daemen et al, 1989) (Muscholl et al, 1979). Fuder et al (1985) also demonstrated an inhibition of the NA overflow using this selective muscarinic agonist at concentrations of 1 and 10 M in guinea-pig isolated atria. In our model, infusion of MCh (0.3pgmin-1) has no effect on the basal NA level, indicating that possible interfering effects of MCh like vasodilatation or bradycardia have no influence on the plasma NA level measured in the portal vein.…”
Section: Discussionmentioning
confidence: 76%